Impact of Service Quality, Promotion, and Customer Satisfaction on Repurchase Decision at Kopinan24 Jepara - Munir, Syamsul; Ali, A. (Manunggal Halim Jaya, 2026)
This study investigates the impact of service quality, promotion, and customer satisfaction on repurchase decisions among Kopinan24 customers in Jepara. This study uses a quantitative approach. The type of data used in this study is primary data, which is then analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) through SmartPLS 0.4. SEM-PLS is a multivariate analysis technique based on components or variances, combining factor analysis and regression analysis to examine the relationships between latent variables in a complex model. Data were collected through questionnaires, with a total of 98 respondents selected using the Roa Purba formula and purposive sampling technique. The results of the study indicate that service quality hurts repurchase decisions, while promotion and customer satisfaction have a positive and significant effect on repurchase decisions. These findings can be used by Kopinan24 Jepara as a consideration for increasing sales through the enhancement of customer repurchase decisions.